Embedding Health-Related Social Needs Screening and Resource Navigation in a U.S. Forensic Asylum Clinic: A Pilot Intervention - Allison Arteaga Argumedo; Manami T. Uechi; Matthew G. Gartland; Altaf Saadi (Journal of Primary Care & Community Health)
Background: Despite increased focus on social determinants of health, little is known about screening and intervention for asylum seekers, a highly marginalized group. We present the feasibility of a pilot social needs screening and resource navigation program at the Massachusetts General Hospital (MGH) Asylum Clinic in Boston, Massachusetts. Methods: Clinicians and staff referred patients who had a forensic evaluation in the clinic for screening. We screened across ten domains: (1) Housing and utilities, (2) Food security, (3) Access to healthcare, (4) Transportation, (5) Education/ Literacy, (6) Employment, (7) Childcare, (8) Disability/Disabling conditions, (9) Psychosocial well-being, and (10) Personal safety. Results: From April 2021 to June 2022, we evaluated 118 patients in the clinic. Twenty-eight (24%) completed screening. Their average age was 35.5 years (range = 18-67) and 50% were men. They came from 11 countries, with Uganda (25%), Cameroon (14%), El Salvador (14%), and Ecuador (14%) most represented. Most common needs were access to healthcare (86%), employment (46%), psychosocial wellbeing (43%), and education (43%). Applicants also typically screened positive for multiple domains (mean = 3.3, SD = 2.2, range = 1-8 domains). Conclusion: Our pilot social needs screening and resource navigation program in an academic asylum clinic demonstrates the model’s feasibility. Future studies should explore patient experiences and outcomes following referral.